The Effect of Local Wisdom-Integrated Problem-Based Learning (PBL) Models on Learning Outcomes in Temperature and Heat Concepts - Pilobu, Muznawaty; Odja, Abdul Haris; Xavier, Felipe; Fathan, Suparmin; Abdjul , Tirtawaty; Payu, Citron S.; Pikoli, Masrid; Yusuf, Muhammad; Mursalin, Mursalin; Ali, Ramli R. (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to analyze the effect of local wisdom-based Problem Based Learning (PBL) on junior high school students' learning outcomes in temperature and heat. The method used was a quantitative experiment with a one-group pretest–posttest design; the independent variable was PBL based on local wisdom integrated through Google Sites (e-modules, worksheets, videos, and contextual tasks), while the dependent variable was learning outcomes measured by achievement tests that had been validated by experts and declared to be highly valid. Data analysis included descriptive statistics, Shapiro–Wilk test for normality, Wilcoxon Signed-Rank test for paired comparisons, and N-Gain for effectiveness. The results show a significant increase: the class average increased from 45 to 84 and from 41 to 84; the posttest data was not normal, so Wilcoxon was used with results of Z = 4.111 and Z = 4.021 (p < 0.001), confirming a significant difference between the pretest and posttest. The average N-Gain = 0.69 (moderate category) with individual distribution in the moderate to high range, indicating that PBL based on local wisdom is effective in strengthening conceptual understanding and encouraging learning engagement. It is recommended to continuously integrate the local cultural context into science units through digital platforms, strengthen teacher training to facilitate PBL, and conduct further research with control groups, larger samples, and mixed approaches to examine conceptual changes and misconception reduction more comprehensively. It is recommended that local cultural contexts be continuously integrated into science units through digital platforms, that teacher training be strengthened to facilitate PBL, and that further research be conducted with control groups, larger samples, and mixed approaches to examine conceptual changes and misconception reduction more comprehensively.